Alteration of Oriented Deposition of Cellulose Microfibrils by Mutation of a Katanin-Like Microtubule-Severing Protein - Burk, David H. (American Society of Plant Biologists, 2002)
It has long been hypothesized that cortical microtubules (MTs) control the orientation of cellulose microfibril deposition, but no mutants with alterations of MT orientation have been shown to affect this process. We have shown previously that in Arabidopsis, the fra2 mutation causes aberrant cortical MT orientation and reduced cell elongation, and the gene responsible for the fra2 mutation encodes a katanin-like protein. In this study, using field emission scanning electron microscopy, we found that the fra2 mutation altered the normal orientation of cellulose microfibrils in walls of expanding cells. Although cellulose microfibrils in walls of wild-type cells were oriented transversely along the elongation axis, cellulose microfibrils in walls of fra2 cells often formed bands and ran in different directions. The fra2 mutation also caused aberrant deposition of cellulose microfibrils in secondary walls of fiber cells. The aberrant orientation of cellulose microfibrils was shown to be correlated with disorganized cortical MTs in several cell types examined. In addition, the thickness of both primary and secondary cell walls was reduced significantly in the fra2 mutant. These results indicate that the katanin-like protein is essential for oriented cellulose microfibril deposition and normal cell wall biosynthesis. We further demonstrated that the Arabidopsis katanin-like protein possessed MT-severing activity in vitro; thus, it is an ortholog of animal katanin. We propose that the aberrant MT orientation caused by the mutation of katanin results in the distorted deposition of cellulose microfibrils, which in turn leads to a defect in cell elongation. These findings strongly support the hypothesis that cortical MTs regulate the oriented deposition of cellulose microfibrils that determines the direction of cell elongation.